Mengantisipasi Kegagalan Islamisasi Sains Dalam Lembaga Pendidikan Islam - Mukani, Mukani (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2015)
Modern society succeeded in developing science and advanced technology to solve life problem. However, it is also not able to grow akhlaq al-karimah. This paper looks for solutions to overcome the tragedy of modern society by focusing the study on the effort to integrate science with religion, through the concept of Islamization of science, born out of a dichotomous concept between religion and science developed by the West and the culture of modern society. The development of science in Islam not only believes in the truths of human senses, logic and ethics, but also acknowledges and believes transcendental truths (Divinity). This suggests that the Islamic conception of science is integral to ethics and morals. Islam does not accept the secularization of science from value or science of virtue (wisdom). The way in which operational normative concepts become objective and empirical is the syntactic and analytic approach. While the model of Islamization saisn which can be developed in looking at the era of globalization is a model of Purification, Modernization of Islam model and Neo-Modernist model. The Islamization of this science may only be done well if a permanent facility or container is available in the form of an Islamic educational institution, especially at the university level.